Análisis y control estadístico de la merma en la cadena de suministros de una empresa Retail – Trujillo 2014 - Guevara Ponce, Victor Manuel (2014)
This thesis aims to conduct analysis and control of shrinkage through statistical tools to diagnose; finding the causes and limits of statistical inventory control oriented reduction of waste produced in a supply chain Retail companies of the city of Trujillo._x000D_ The information is obtained from the database of the company, which uses the SAP EASY ACCESS program where inventory is recorded in inventory shrinkage produced in a respective month, the count is done weekly but monthly accounts, the company Retail the main item in the sale of housewares and home use, so the store is divided into sections called worlds, database records information from January 2011 until September 2014, which will work to obtain the research objective._x000D_ The causes of the decline of the collected data is determined as well as distributed in the respective sections and / or worlds , supported by statistical software control charts is performed to determine whether the decline is under the control limits._x000D_ The main results point to contribute to a greater commitment of administrative company about the problem, to prevent losses under greater efficiency in distributing supplies company Retail